12 Days Under Ice - an historic AUV deployment in the Canadian High Arctic - Kaminski, C; Crees, T; Ferguson, J; Forrest, AL; Williams, J; Hopkin, D; Heard, G (2010 IEEE/OES Autonomous Underwater Vehicles, 2010)
In March and April 2010, an International SubmarineEngineering (ISE) Explorer Autonomous Underwater Vehicle(AUV), built for Natural Resources Canada (NRCan), wasdeployed to Canadas High Arctic. Its mission was to undertakeunder-ice bathymetric surveys in support of Canadas UnitedNations Convention on the Law of the Sea (UNCLOS) OuterContinental Shelf claim. During this deployment several undericerecords were broken and several new technologies weredemonstrated. This achievement was in part the result of the developmentwork that ISE and Defence Research and Development Canada(DRDC) undertook from 1993 to 1996 on the Theseus AUVduring the Spinnaker program. During this program Theseussuccessfully completed two 200 km under-ice missions from CFSAlert on Ellesmere Island. NRCans AUV is an ISE Explorer class vehicle, with severalinnovative additions to make it suitable for Arctic survey work.Most notable are a 4000 m depth rated variable ballast system, a1500 Hz long range homing system, and under ice charging anddata transfer capabilities. A Short Range Localization (SRL)system was also developed for close range positioning. Thehoming and SRL systems were developed by Canadian defensescientists and engineers at DRDC. The Explorers range wasextended to approximately 400 km by adding an additional hullsection to accommodate extra batteries. The Main Camp near Borden Island (7813.50N, 11238.87W)was the launch site for the AUV. It was launched from an 8 m by2.5 m ice-hole, cut through 2 3 m of thick ice. After several testdives its first mission was a transit to a Remote Camp, over 300km to the northwest. The AUV autonomously homed into theRemote Camp and was successfully docked at the ice-hole where,without being removed from the water, it was charged andsurvey data was downloaded, all through a 1.5 m square ice hole.Subsequently, a second survey mission greater than 300 km inround trip length was undertaken, after which the AUV returnedback to the Remote Camp. Finally, the vehicle embarked on areturn mission to the Main Camp for recovery. From beginningto end, the AUV spent nearly 12 days under the ice before beingsuccessfully recovered. In total, close to 1000 km of under ice survey was accomplishedbetween the AUV launch, Remote Camp mission, and recovery.The AUV reached depths of 3160 m and transited at an averagespeed of 1.5 m/s at an altitude of 130 m off the seabed. ISE andDRDC are now preparing for a 2011 deployment to collectadditional data UNCLOS data. Aspects of the pre-deployment that will be presented includefail-safe provisions, mission planning, risk assessment, andmission logistics. Operational aspects to be discussed will includedealing with AUV operations in the extreme cold, initialization ofthe inertial navigation system, under-ice acoustics, acoustichoming to the recovery site and the procedures for recovery.